1993
DOI: 10.1177/002199839302701202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multiple Delaminations on Compressive Buckling Behaviors of Composite Panels

Abstract: Compressive buckling stability of composite panels with through-width, equally spaced multiple delaminations are investigated analytically and experimentally. An analytical method is formulated on the basis of Rayleigh-Ritz approximation technique. Timoshenko type shear effects are included. An experiment and a finite element analysis are also conducted on the present model. The analytical results agree very well with the experimental and finite element results. The buckling load, which is the compressive stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 9 publications
(10 reference statements)
1
26
0
Order By: Relevance
“…As mentioned in the reference (20) , the delamination cracks usually locate in a helical pattern. In the present study, to simplify the model of the multi-crack effect, the helical pattern is not adopted here.…”
Section: Fem Analysesmentioning
confidence: 90%
See 1 more Smart Citation
“…As mentioned in the reference (20) , the delamination cracks usually locate in a helical pattern. In the present study, to simplify the model of the multi-crack effect, the helical pattern is not adopted here.…”
Section: Fem Analysesmentioning
confidence: 90%
“…In reality the actual damage to the laminated CFRP has complicated multiple delamination cracks (18) . It is impossible to analyze the multiple delamination cracks in detail using 3-D FEM analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Suemasu has studied the buckling behavior of delaminated composite laminates by using classical laminate plate theory (CLPT) and first order shear deformation theory (FSDT) [7,8]. Adan et al have solved the governing differential equation for beams with multiple through the width delaminations to find the buckling load [9].…”
Section: Introductionmentioning
confidence: 99%
“…He also investigated the load-displacement behavior, and the corresponding growth of the delamination. Several other researchers [8][9][10] also studied the delamination growth and the corresponding stability analysis. It was observed that compressive buckling stress suddenly dropped as the multiple delaminations reached a certain length.…”
Section: Introductionmentioning
confidence: 99%